2018
DOI: 10.1063/1.5054155
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of InN thin films by plasma-enhanced atomic layer deposition

Abstract: In this study, we report on the growth of crystalline InN thin films by plasma-enhanced atomic layer deposition (PE-ALD). By systematically investigating the growth parameters, we determined the process window for crystalline InN films growth by PE-ALD. Under the optimal conditions, we compared Si (100), Al2O3 (0001), and ZnO (0001) substrates with different lattice mismatches to InN. High resolution X-ray diffraction (HR-XRD) measurements showed that we obtained the epitaxial InN thin film on the ZnO (0001) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The presence of the (0002) peak in both the 2θ-θ and GIXRD measurement, indicate that some InN grains are orientated along the c-axis whilst others are titled with respect to the c-axis. to 4H-SiC (hkil) and 6 poles to InN (10)(11). Note that the poles for 4H-SiC and InN overlap.…”
Section: Xrd Analysis Of Inn On Si(100) and Sicmentioning
confidence: 98%
See 1 more Smart Citation
“…The presence of the (0002) peak in both the 2θ-θ and GIXRD measurement, indicate that some InN grains are orientated along the c-axis whilst others are titled with respect to the c-axis. to 4H-SiC (hkil) and 6 poles to InN (10)(11). Note that the poles for 4H-SiC and InN overlap.…”
Section: Xrd Analysis Of Inn On Si(100) and Sicmentioning
confidence: 98%
“…144 (17) 168 (15) 111(10) 0 55(11) 0 N(10) 120 (3) 120(3) 119(3) 1(1) 0(1) 0(1) C(11) 217 (17) 240 (20) 138(15) 0 99(14) 0 N(11) 133 (14) 174 (17) 153 (12) 13 (11) 33 (11) 66(12) C(13) 212 (9) 212(9) 212(9) 0(1) 0(1) 0(1) C (21) (8) 202 (8) 202(8) 0(1) 0(1) 0(1) C(24) 182 (5) 183 (5) 183(5) 0(1) -1(1) 0(1) C(18) 170 (10) 221 (11) 188(11) -85(10) -30(10) -58(7) __________________________________________________________________________ Figure S6. Enthalpy at 250°C of the decomposition paths.…”
Section: X-ray Crystallographic Analysismentioning
confidence: 99%
“…Differential Scanning Calorimetry of 1, which shows two distinct exothermic events between 150-180 and 220-280°C. (24) 3023 (11) 1315 (13) 10813 (19) 183 (5) C (18) 37 (11) 950 (13) 7240 (20) 193 (…”
Section: Synthesis Of Tris(13-diisopropyltriazenide)indium(iii) (1)mentioning
confidence: 99%
“…In this regard, plasma-enhanced atomic layer deposition (PE-ALD) becomes an attractive choice as it offers surface-chemistry driven atomic-scale precision material growth at low substrate temperatures. 17,[25][26][27][28][29][30][31][32] The main advantages of ALD compared to other thin lm growth techniques are sub-nanometer precision thickness control, low-temperature growth, ultimate conformality, and large-area uniformity. 33,34 To date, there have been multiple efforts towards low-temperature InN growth via PE-ALD.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 To date, there have been multiple efforts towards low-temperature InN growth via PE-ALD. 17,[30][31][32][35][36][37][38][39][40][41] Initial epitaxial growth of InN at sub-300 C was achieved by plasma-enhanced atomic layer epitaxy (PE-ALE) where the lms exhibited substrate-dependent varying crystallographic orientations. 17,36 In a relatively recent study, PE-ALD of monocrystalline InN lms has also been reported at 250 C using N 2 -plasma on lower-lattice-mismatched ZnO/Al 2 O 3 substrates, where the lms were fully relaxed with no voids or interlayers at the interfaces.…”
Section: Introductionmentioning
confidence: 99%